2020
DOI: 10.1177/1178221820949262
|View full text |Cite
|
Sign up to set email alerts
|

Truck Drivers’ Cigarette Smoking and Preferred Smoking Cessation Methods

Abstract: Introduction: Some studies show that truck drivers use tobacco and other stimulants to stay awake as they drive. Despite their increased risks for many of tobacco-related health disparities, there is limited engagement of truck drivers in smoking cessation programs. The objective of this study was to describe smoking characteristics and identify their preferred smoking cessation methods among truck drivers. Methods: This was a cross-sectional mixed methods study. Participants were truck drivers recruited at tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…1,3 Older drivers have had prolonged exposure to risk factors such as a sedentary lifestyle and smoking and more time to develop colorectal polyps and cancer-causing mutations. 1,7,[12][13][14]17,18 Due to the increased exposure to CRC risk factors among truck drivers 12,15,24 amplified awareness and education about the importance of early-detection screening for CRC may aid in reducing CRC morbidity and mortality in this population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,3 Older drivers have had prolonged exposure to risk factors such as a sedentary lifestyle and smoking and more time to develop colorectal polyps and cancer-causing mutations. 1,7,[12][13][14]17,18 Due to the increased exposure to CRC risk factors among truck drivers 12,15,24 amplified awareness and education about the importance of early-detection screening for CRC may aid in reducing CRC morbidity and mortality in this population.…”
Section: Discussionmentioning
confidence: 99%
“…7,[12][13][14] Obesity and tobacco use are twice as high among truckers as they are in the overall U.S. adult labor force, 15,16 and previous research has shown that truck drivers often smoke cigarettes to stay awake. 1,17,18 Truck drivers also often have few nutritious options available to them while commuting, 19 face challenges to eating healthily, 20 and have high rates of metabolic syndrome. 21,22 High-fat diets have been associated with poor health among truck drivers.…”
Section: Purposementioning
confidence: 99%
“…The studies were conducted on five continents and in 10 countries, South Africa [25,32,35], Germany [22], Australia [26,36], Brazil [21], Canada [27,30], Spain [34], United States [14,15,17,19,23,24,28,29,31,33], Finland [20], Iran [16], and Sweden [18]. In 2018, eight articles were published [14][15][16][17][18][19][20][21]; followed by six publications in 2019 [22][23][24][25][26][27], two in 2020 [28,29], five in 2021 [30][31][32][33][34], and two publications in 2022 [35,36].…”
mentioning
confidence: 99%
“…The 23 studies analyzed aimed to evaluate sleep [19][20][21], sleep and mental health [23,24,29], sleep and risk of cardiovascular disease [32], Diet [22], diet and physical activity [26], risk of cardiometabolic disease [17,18]. The prevalence of obesity and its association with systemic arterial hypertension and diabetes mellitus [35], sexual health [14], and sexually transmitted infection (STI) [33], risk of musculoskeletal injury [15], fatigue and occupational safety [34], physical and mental health [25,36], smoking [28], symptoms of depression [26] and about the health of truck drivers in the early years of the COVID-19 pandemic [30].…”
mentioning
confidence: 99%
See 1 more Smart Citation